Long-term effectiveness and safety of sirolimus drug-eluting stents - Bikkina M (Dove Medical Press, 2011)
Mahesh Bikkina, Jayanth KoneruSt Joseph Regional Medical Center, Paterson, Seton Hall University, NJ, USAAbstract: The root cause of coronary artery disease is atherosclerosis, ie, intraluminal narrowing (stenosis) of the arteries that supply blood to tissues of the heart. The introduction of the drug-eluting stent over the past decade has revolutionized the field of interventional cardiology. It is used extensively in clinical practice for the treatment of coronary artery disease. The first drug-eluting stent to receive US Food and Drug Administration approval was the sirolimus-eluting stent. Recently, two other stent analogs of sirolimus were approved, ie, the zotarolimus-eluting stent and the everolimus-eluting stent. However, concern has arisen in recent years about the long-term safety and efficacy of drug-eluting stents, due to the occurrence of late adverse clinical events, such as stent thrombosis. This review focuses on clinical studies that have been performed with the sirolimus-eluting stent or its analogs. We discuss the pharmacology, safety, and various therapeutic options that exist when choosing stents for coronary artery disease. Our aim is to provide a thorough review of the long-term efficacy and safety of sirolimus drug-eluting stents, and also to discuss currently approved and promising investigational drug-eluting stents, in an effort to provide insight into how these stents are currently evolving and generate further investigation in this area.Keywords: drug-eluting stent, long-term safety, sirolimus